Hubungan antara Body Image dan Penerimaan Sosial terhadap Kepercayaan Diri Pengguna Instagram Mahasiswa S1 Fakultas Ilmu Pendidikan dan Psikologi Universitas Negeri Semarang - Istna Slavi Aji; Muslikah Muslikah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The focus of this research is to examine the relationship between body image and social acceptance towards the self-confidence of Instagram users. This study uses a correlational quantitative approach with data collection techniques utilizing interviews, questionnaires, and psychological scales in the form of Likert scales. The population and sample of this research are students S1 from the Faculty of Education and Psychology who are Instagram users. The validity test of this study is supported by the Statistical Product and Services Solutions (SPSS) version 26 using the Pearson product-moment formula. The instrument's validity is measured based on the correlation significance test > at a significance level of 5%. The research results show that body image, social acceptance, and self-confidence of Instagram users among undergraduate students of the Faculty of Education and Psychology at Universitas Negeri Semarang are in the moderate category. Body image and social acceptance have a relationship with self-confidence of 56%. The remaining percentage is influenced by predictors or other variables that were not examined in this study.